2008
DOI: 10.1159/000143220
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone-Induced Analgesic Effects in a Bone Cancer Pain Model in Mice

Abstract: The femur bone cancer pain model was developed by implanting mouse osteolytic tumor cells (NCTC 2472) into the intramedulla of the femur in C3H/HeN mice. In vivo imaging analysis revealed that the implanted tumor cells grew progressively over 14 days. Associated with the tumor growth, guarding behavior, which was an indication of ongoing pain, time-dependently increased. Limb use abnormality and allodynia, which were indications of ambulatory and neuropathic pain, respectively, also appeared. The analgesic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
1
4
0
1
Order By: Relevance
“…The preliminary experiments demonstrated that the onset time of oXY using the systemic administration route was 15 min, with peak efficacy after 30 min and efficacy lasting for 2-4 h (Fig. 2B), which was consistent with the results of previous studies (7,28,36,37). as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The preliminary experiments demonstrated that the onset time of oXY using the systemic administration route was 15 min, with peak efficacy after 30 min and efficacy lasting for 2-4 h (Fig. 2B), which was consistent with the results of previous studies (7,28,36,37). as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The administration of saline (0.9%) and oXY hydrochloride injection (oxynorm; 10 mg/ml; napp Pharmaceuticals, ltd.) was randomized (n=21). oXY was diluted to 0.5 mg/ml with 0.9% saline and intraperitoneally injected at a dose of 2.5 mg/kg twice daily for 5 consecutive days from the 8th day after the injection of tumor cells to establish the ciBP model, as described previously (7,17,28,29). Saline was used in the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Opioidler, kemik metastazına bağlı ağrının medikal tedavisinde temel taşlardır. Preklinik araştırmalar farklı opioidler için etkinliğin değişken olabileceğini göstermekle birlikte (14), klinik kullanımda kemik metastazlarının ağrı tedavisinde daha üstün etkinlik gösteren bir opioid tanımlanamamıştır. Bazı opioidler hasta için diğer opioidlerden daha fazla analjezi sağlayabilir ve bunu belirlemenin tek yolu "deneme ve yanılma" dır.…”
Section: Opioidlerunclassified
“… Selected pharmacological interventions with positive effects in animal models of CIBP: Trk inhibitor (ARRY-470); 79 BDNF siRNA; 82 P2X 3 antagonist (AF-353); 138 TRPV1 antagonist (JNJ-17203212); 125 IL-1 receptor antagonist (anakinra); 103 anti-MCP-1 antibody; 114 anti-CX3CR1 antibody; 110 , 111 anti-TNFα antibody (etanercept); 27 anti-NGF antibody; 75 , 77 sulfasalzine; 87 thalidomide; 105 gabapentin; 179 opioids (morphine, oxycodone); 180 , 181 alendronate; 177 cisplatin + 89 SR; 182 anti-RANKL antibody (denosumab); 183 Cox-2 inhibitor (MF tricyclic); 20 zoledronic acid; 176 p38 MAPK inhibitor (SB203580); 184 osteoprotegerin; 41 , 42 CB2 agonist (JWH015); 101 ibandronate; 44 , 45 risedronate; 44 , 46 anti-PTHrP antibody; 56 cathepsin K inhibitor; 178 TGFβ type I receptor kinase inhibitor (LY2109761); 57 and chemotherapeutics. Trk inhibitor, tropomyosin receptor kinase inhibitor; BDNF siRNA, brain-derived neurotrophic factor small interfering RNA; P2X 3 antagonist, P2X purinoceptor 3 antagonist; TRPV1 antagonist, transient receptor potential vanilloid type 1 antagonist; IL-1 receptor antagonist, interleukin-1 receptor antagonist; anti-MCP-1 antibody, anti-monocyte chemoattractant protein-1 antibody; anti-CX3CR1 antibody, anti-fractalkine receptor antibody; anti-TNFα antibody, antitumor necrosis factor-α antibody; anti-NGF antibody, anti-nerve growth factor antibody; anti-RANKL antibody, anti-receptor activator of nuclear factor κB ligand antibody; CB2 agonist, cannabinoid receptor 2 agonist; anti-PTHrP antibody, anti-parathyroid hormone related protein antibody.…”
Section: Figurementioning
confidence: 99%